THE RELATIONSHIP BETWEEN UNEMPLOYMENT RATES, ECONOMIC INCENTIVES, AND PROPERTY CRIME - Danang Rahmat Surono; Gunawan Widjaja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study examines the relationship between unemployment rates, economic incentives, and property crime through a literature review. High unemployment rates are often a major factor that drives individuals to commit property crimes in order to meet their economic needs. On the other hand, economic incentives such as social assistance, skills training programmes, and economic subsidies play an important role in reducing the motivation to commit crimes by providing legitimate alternatives for income. This study highlights that the effectiveness of economic incentives is greatly influenced by the quality of governance, fair distribution, and integration with other social policies. The study finds that combating property crime requires a multisectoral approach that synergises unemployment reduction, economic incentives, social strengthening, and improved education to create a safe and productive society.